Genetic correlations between categorical morphological traits in Nelore cattle by applying Bayesian analysis under a threshold animal model - Faria, C. U.; Pires, B. C.; Vozzi, A. P.; Magnabosco, C. U.; Koury Filho, W.; Viu, M. A. O.; Oliveira, Henrique Nunes de [UNESP]; Lobo, R. B. (Wiley-Blackwell, 2010)
P>In this study, Bayesian analysis under a threshold animal model was used to estimate genetic correlations between morphological traits (body structure, finishing precocity and muscling) in Nelore cattle evaluated at weaning and yearling. Visual scores obtained from 7651 Nelore cattle at weaning and from 4155 animals at yearling, belonging to the Brazilian Nelore Program, were used. Genetic parameters for the morphological traits were estimated by two-trait Bayesian analysis under a threshold animal model. The genetic correlations between the morphological traits evaluated at two ages of the animal (weaning and yearling) were positive and high for body structure (0.91), finishing precocity (0.96) and muscling (0.94). These results indicate that the traits are mainly determined by the same set of genes of additive action and that direct selection at weaning will also result in genetic progress for the same traits at yearling. Thus, selection of the best genotypes during only one phase of life of the animal is suggested. However, genetic differences between morphological traits were better detected during the growth phase to yearling. Direct selection for body structure, finishing precocity and muscling at only one age, preferentially at yearling, is recommended as genetic differences between traits can be detected at this age.
Keywords: Bayesian; Beef cattle; Visual score; Threshold model; Genetic parameter